2012
DOI: 10.1111/j.1365-2850.2012.01930.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of staff training on the violence prevention and management climate in psychiatric inpatient units

Abstract: Violence prevention and management is an important part of inpatient psychiatric nursing and specific staff training is regarded essential. The training should be based on primary, secondary and tertiary prevention. In Stockholm, Sweden, the Bergen model is a staff-training programme that combines this preventive approach with the theoretical nursing framework of the City model that includes three staff factors: positive appreciation of patients, emotional regulation and effective structure. We evaluated this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 32 publications
(39 reference statements)
1
69
0
3
Order By: Relevance
“…[35] Patients and staff in Sweden indicated that the rules in the ward are good for incivility and violence prevention. [47]…”
Section: Discussionmentioning
confidence: 99%
“…[35] Patients and staff in Sweden indicated that the rules in the ward are good for incivility and violence prevention. [47]…”
Section: Discussionmentioning
confidence: 99%
“…In this study, internal violence was more strongly associated with poor health. Current occupational safety education protocols and management processes more often focus on external violence than internal violence; therefore, internal violence remains less addressed (Bjorkdahl, Hansebo, & Palmstierna, 2013;Dillon, 2012;Stagg & Sheridan, 2010). Current occupational safety education protocols and management processes more often focus on external violence than internal violence; therefore, internal violence remains less addressed (Bjorkdahl, Hansebo, & Palmstierna, 2013;Dillon, 2012;Stagg & Sheridan, 2010).…”
Section: N/mean %/Sdmentioning
confidence: 99%
“…Encouraging findings do exist in this body of work; the majority of studies found that trained employees tend to report increased confidence in comparison to untrained (see Bjorkdahl et al . ; Richter et al . ).…”
Section: Clinician‐related Phenomenamentioning
confidence: 99%